4-1BB Signaling Boosts the Anti-Tumor Activity of CD28-Incorporated 2nd Generation Chimeric Antigen Receptor-Modified T Cells - Dai, Qiang; Han, Ping; Qi, Xinyue; Li, Fanlin; Li, Min; Fan, Lilv; Zhang, Huihui; Zhang, Xiaoqing; Yang, Xuanming (Frontiers in Immunology, 2020)
While chimeric antigen receptor-modified T (CAR-T) cells have shown great success for the treatment of B cell leukemia, their efficacy appears to be compromised in B cell derived lymphoma and solid tumors. Optimization of the CAR design to improve persistence and cytotoxicity is a focus of the current CAR-T study. Herein, we established a novel CAR structure by adding a full length 4-1BB co-stimulatory receptor to a 28Z-based second generation CAR that targets CD20. Our data indicated that this new 2028Z-4-1BB CAR-T cell showed improved proliferation and cytotoxic ability. To further understand the mechanism of action, we found that constitutive 4-1BB sensing significantly reduced the apoptosis of CAR-T cells, enhanced proliferation, and increased NF-B pathway activation. Consistent with the enhanced proliferation and cytotoxicity in vitro, this new structure of CAR-T cells exhibited robust persistence and anti-tumor activity in a mouse xenograft lymphoma model. This work provides evidence for a new strategy to optimize the function of CAR-T against lymphoma.